2019
DOI: 10.1002/jmrs.318
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of an advanced practice role in palliative radiation therapy

Abstract: Introduction The purpose of the study was to evaluate the palliative advanced practice radiation therapy (APRT) role with respect to the impact on waiting times for patients from referral to radiation treatment delivery, the ability of the APRT to define palliative radiation therapy fields and patient satisfaction. The evaluation of the impact of the APRT role and referral pathway on patient waiting times has been previously published. Methods Patients were allocated to two different pathways; APRT and standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…From this, it may be suggested that radiographer-led roles have the potential to improve access to palliative radiotherapy through reduced waiting times. 26,27 Statistical analyses in both studies show a high correlation between radiographer's and clinical oncologist's plans, supporting the authors' claim of equivalence in work quality. Their conclusion that radiographer-led pathways can reduce waiting times is, however, a supposition.…”
Section: Discussionsupporting
confidence: 60%
“…From this, it may be suggested that radiographer-led roles have the potential to improve access to palliative radiotherapy through reduced waiting times. 26,27 Statistical analyses in both studies show a high correlation between radiographer's and clinical oncologist's plans, supporting the authors' claim of equivalence in work quality. Their conclusion that radiographer-led pathways can reduce waiting times is, however, a supposition.…”
Section: Discussionsupporting
confidence: 60%
“…In Brisbane, Australia, a 2014e2015 study of 150 patients showed that an advanced practice radiation therapist reduced the mean time from referral for palliation to consultation from 3.2 to 1.4 days, the mean time from referral to treatment from 8.1 to 3.5 days and increased the rate of patients assessed and treated on the same day from 9% to 33% [45]. Another report from the same group showed that 82/92 (89%) of field borders independently created by the therapist for a variety of palliative indications were deemed clinically acceptable by the patient's radiation oncologist [46]. Fields were considered acceptable if the clinical outcome to the patient would not have been meaningfully different compared with the outcome expected from the radiation oncologist's fields.…”
Section: Advancing Roles Within the Multidisciplinary Teammentioning
confidence: 98%
“…The APRT role at ROPART has been formally evaluated, with the results showing a reduction in wait times for palliative patients from referral to delivery of radiotherapy treatment and reduced hospital visits. Additionally, the ability of the APRT to define palliative radiotherapy treatment volumes when compared with a radiation oncologist has been successfully evaluated, and the impact of the role when reviewing overall patient satisfaction is positive [5,6].…”
Section: The Advanced Palliative Radiation Therapist Role E South Brimentioning
confidence: 99%